2019
DOI: 10.1002/aelm.201800770
|View full text |Cite
|
Sign up to set email alerts
|

1D ZnSSe‐ZnSe Axial Heterostructure and its Application for Photodetectors

Abstract: possessing high photocurrent gain, fast response speed, high photosensitivity, wide response wavelength, and multiband photodetection are highly desired. [1][2][3][4] For this purpose, nanowires with large surface-to-volume ratio and quantum confinement effect show huge advantages over the bulk and thin film counterparts for fabrication of high performance photodetectors. [5][6][7][8][9][10] Since the discovery of carbon nanotubes, there are many reports about the photodetectors based on various 1D inorganic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 47 publications
(41 reference statements)
0
16
0
Order By: Relevance
“…In 2019, Mu et al reported the development of a photodetector by using high-quality ZnS 0.49 Se 0.51 /ZnSe axial heterojunction nanowires (HNWs) with a uniform diameter distribution of 50-100 nm. 10 The axial ZnS 0.49 Se 0.51 /ZnSe HNWs were synthesized using an improved two-step CVD strategy. It is found that the axial ZnS 0.49 Se 0.51 /ZnSe HNW based photodetector exhibits a wide photoresponse range of 360-480 nm (Fig.…”
Section: D and 2d Nanostructure Based Photodetectorsmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2019, Mu et al reported the development of a photodetector by using high-quality ZnS 0.49 Se 0.51 /ZnSe axial heterojunction nanowires (HNWs) with a uniform diameter distribution of 50-100 nm. 10 The axial ZnS 0.49 Se 0.51 /ZnSe HNWs were synthesized using an improved two-step CVD strategy. It is found that the axial ZnS 0.49 Se 0.51 /ZnSe HNW based photodetector exhibits a wide photoresponse range of 360-480 nm (Fig.…”
Section: D and 2d Nanostructure Based Photodetectorsmentioning
confidence: 99%
“…have been widely used for the fabrication of UVPDs in recent years due to their large bandgap, high exciton binding energy and exciton gain, good optical properties, and excellent thermal and environmental stabilities. [7][8][9][10] In addition, II-VI group semiconductors have higher electron and hole mobilities than those of other semiconductor materials with a similar bandgap. 11 Another important property is the direct band structure of II-VI group semiconductors, which determines the interband radiative recombination of electrons and holes, and the high efficiency of electron-hole pair generation after the absorption of photons.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] In terms of basic optical properties, ZnSe can used in solar cells, protective and antireflection coating, blue laser diodes, light-emitting diodes, photodetector, and sensors. [14][15][16][17][18][19][20][21][22] With the rapid development of lasers, traditional linear optical devices have not been able to meet some specific requirements of high power laser and military fields. Therefore, nonlinear optical absorption (NOA) behaviors of chalcogenide thin films gradually attracted much attention of the researchers.…”
Section: Doi: 101002/crat202000177mentioning
confidence: 99%
“…ZnSe, a significant member of the II-VI semiconductor compounds, which is a light yellow solid compound with a band gap of 2.70 eV 8 . It is an excellent candidate for fabrication of visual displays and photodetectors, etc [9][10][11][12] . It is an essential prerequisite for material's synthesis and application to investigate the fundamental physical properties of ZnSe.…”
mentioning
confidence: 99%